Insolvency regimes, zombie firms and capital reallocation - Adalet McGowan, Müge (OECD Publishing, 2017)
This paper explores cross-country differences in the design of insolvency regimes and their potential links with two inter-related sources of labour productivity weakness: the survival of "zombie" firms (firms that would typically exit in a competitive market) and capital misallocation. New cross-country policy indicators of insolvency regimes are constructed based on countries' responses to a recent OECD questionnaire, which aimed to better capture the key design features of insolvency which impact the timely initiation and resolution of insolvency proceedings. According to these metrics, cross-country differences in the design of insolvency regimes are significant. Firm level analysis shows that reforms to insolvency regimes which reduce barriers to corporate restructuring and the personal cost associated with entrepreneurial failure may reduce the share of capital sunk in zombie firms. These gains are partly realised via the restructuring of weak firms, which in turn spurs the reallocation of capital to more productive firms. These findings carry strong policy implications, in light of the fact that there is much scope to reform insolvency regimes in many OECD countries and given evidence that rising capital misallocation and the increasing survival of low productivity firms have contributed to the productivity slowdown
Keywords: Economics